Impact of Heat Stress on Ovarian Function and circRNA Expression in Hu Sheep - Jianwei Zou; Lili Wei; Zhihua Mo; Yishan Liang; Jun Lu; Juhong Zou; Fan Wang; Shaoqiang Wu; Hai’en He; Wenman Li; Yanna Huang; Qinyang Jiang (Animals)
Climate change poses an increasing threat to livestock reproduction, with heat stress (HS) known to significantly impair ovarian function. This study aimed to elucidate the impact of HS on ovarian function and circRNA expression profiles in Hu sheep. Twelve ewes were randomly assigned to a control (Con, n = 6) or HS group (n = 6) and exposed to different temperatures for 68 days. Compared with the Con group, HS significantly increased the respiratory rate (108.33 ± 3.72 vs. 63.58 ± 2.42 breaths/min), pulse rate (121.17 ± 3.98 vs. 78.08 ± 3.31 beats/min), and rectal temperature (40.17 ± 0.14 °C vs. 39.02 ± 0.21 °C; p < 0.05). Concurrently, serum antioxidant levels were markedly decreased, including total antioxidant capacity (T-AOC), total superoxide dismutase (T-SOD), and glutathione peroxidase (GSH-Px) (p < 0.05). Histological analysis revealed a significant reduction in the numbers of primordial, primary, secondary, and mature follicles, alongside an increase in antral follicles (p < 0.05). TUNEL staining demonstrated enhanced granulosa cell apoptosis (p < 0.05), accompanied by the upregulation of pro-apoptotic genes Bax and Caspase-3 and downregulation of the anti-apoptotic gene Bcl-2, as confirmed by qPCR (p < 0.05). CircRNA sequencing identified 152 differentially expressed circRNAs (120 upregulated, 32 downregulated), and enrichment analyses indicated their involvement in apoptosis, mitophagy, and the FoxO signaling pathway. Collectively, these findings demonstrate that HS impairs ovarian physiology and antioxidant defense, induces follicular damage and cell apoptosis, and alters circRNA expression profiles, providing new insights into the molecular mechanisms underlying HS-induced reproductive dysfunction in Hu sheep.